High-Dose, but Not Low-Dose, Aspirin Impairs Anticontractile Effect of Ticagrelor following ADP Stimulation in Rat Tail Artery Smooth Muscle Cells. (6th June 2013) - Grześk, Grzegorz; Kozinski, Marek; Tantry, Udaya S.; Wicinski, Michal; Fabiszak, Tomasz; Navarese, Eliano P.; Grzesk, Elzbieta; Jeong, Young-Hoon; Gurbel, Paul A.; Kubica, Jacek
Abstract : Objective. To compare effects of low- versus high-dose aspirin coadministered with ticagrelor on the reactivity of vascular smooth muscle cells (VSMCs). Methods. Wistar rats were orally administered ticagrelor (10 mg/kg) and/or aspirin (2 or 10 mg/kg) (n = 7 per each of 4 groups) or placebo (n = 9 ) 12 and 2 hours before experiments. Anticontractile effects of ticagrelor were assessed in perfusion solution containing ticagrelor (1 μ M/L). Changes in perfusion pressure proportional to the degree of adenosine diphosphate analogue- (2-MeS-ADP-) and phenylephrine-induced constriction of rat tail arteries were evaluated. Results. Pretreatment with high- but not low-dose aspirin enhanced the reactivity of VSMCs only in endothelium-lined vessels. Suppression of 2-MeS-ADP-induced VSMC contraction by ticagrelor observed in arteries with and without endothelium was maintained in endothelialized arteries pretreated only with low-dose aspirin. For endothelium-denuded vessels and low-dose aspirin we observed a significant reduction of the maximal effect of ticagrelor with no rightward shift of the concentration-response curve for phenylephrine. With high-dose aspirin pretreatment ticagrelor exerted no anticontractile effect. Conclusion. High-dose, but not low-dose, aspirin impairs the anticontractile effect of ticagrelor on ADP-induced VSMC contraction in the rat model. Both the clinical significance and detailed underlying mechanism of our findings require further investigation.